Web-based online sales in Hendra Store - Yahyan, Wahyuni; Sutardjo, Agus; nikolaus, nikolaus (JENTIK, 2023)
When transactions are recorded manually, there are often difficulties in controlling inventory and errors in sales reports. The objective of this research is to develop a sales data processing application that can help store owners manage sales transactions. This research was conducted in Toko Hendra Kota Padang using PHP programming language and MySql as database. The system development method used is SDLC with waterfall model while the tools used to design this system use UML with different diagrams including: Use Case Diagram, Class Diagram, Activity Diagram and Sequence Diagram. It is hoped that this system can support the performance and services of Hendra's Store by facilitating the management of purchasing and sales data.